Vitamin C based nanostructures: potential utility in ocular and transdermal therapy - Palma, Santiago Daniel (2013)
Alkyl vitamin C derivatives (ASCn) combine in their structure a lipophilic and a hydrophilic moiety and exhibit properties of typical surfactant molecules. Self-assembly properties of ASCn depend on the length of n-alkyl fatty chain. ASCn start to aggregate at temperatures (CMT, Krafft point) at which the solubility reaches the critical micellar concentration (CMC). Above this temperature, ASCn can aggregate in micelles or gel phase, depending of alkyl side chain. Upon cooling, for less soluble derivatives (ASC12, ASC14 and ASC16) liquid–crystal structures named coagels are obtained. They are able to solubilize insoluble and unstable drugs, protect them from any possible aggressive environment and promote their permeation through skin and mucosa. These systems possess very interesting properties making ASCn coagels promising pharmaceutical platforms for drug delivery. Results from investigations about all these properties will be described and analyzed in the present review with particular emphasis on the use of these systems for drug administration through ocular and transdermal routes.